In vitro methods to assess drug precipitation in the fasted small intestine – a PEARRL review. (28th June 2018) - O'Dwyer, Patrick J.; Litou, Chara; Box, Karl J.; Dressman, Jennifer B.; Kostewicz, Edmund S.; Kuentz, Martin; Reppas, Christos
Abstract: Objectives: Drug precipitation in vivo poses a significant challenge for the pharmaceutical industry. During the drug development process, the impact of drug supersaturation or precipitation on the in vivo behaviour of drug products is evaluated with in vitro techniques. This review focuses on the small and full scale in vitro methods to assess drug precipitation in the fasted small intestine. Key findings: Many methods have been developed in an attempt to evaluate drug precipitation in the fasted state, with varying degrees of complexity and scale. In early stages of drug development, when drug quantities are typically limited, small‐scale tests facilitate an early evaluation of the potential precipitation risk in vivo and allow rapid screening of prototype formulations. At later stages of formulation development, full‐scale methods are necessary to predict the behaviour of formulations at clinically relevant doses. Multicompartment models allow the evaluation of drug precipitation after transfer from stomach to the upper small intestine. Optimisation of available biopharmaceutics tools for evaluating precipitation in the fasted small intestine is crucial for accelerating the development of novel breakthrough medicines and reducing the development costs. Summary: Despite the progress from compendial quality control dissolution methods, further work is required to validate the usefulness of proposed setups and to increase their biorelevance, particularly in simulating the absorption of drug along the intestinal lumen. Coupling results from in vitro testing with physiologically based pharmacokinetic modelling holds significant promise and requires further evaluation.